Autoinflammation in pyoderma gangrenosum and its syndromic form (pyoderma gangrenosum, acne and suppurative hidradenitis). (16th April 2017) - Marzano, A.V.; Damiani, G.; Ceccherini, I.; Berti, E.; Gattorno, M.; Cugno, M.
Abstract : What's already known about this topic? Pyoderma gangrenosum (PG) is a prototypic neutrophilic dermatosis manifesting as skin ulcers. It may also occur in the context of syndromes like PAPA (pyogenic arthritis, pyoderma gangrenosum and acne) and PASH (pyoderma gangrenosum, acne and suppurative hidradenitis). Although an autoinflammatory origin has been demonstrated for its syndromic forms, to date a specific genetic background related to autoinflammation has not been proven for pyoderma gangrenosum. What does this study add? The clear‐cut increase in skin expression of interleukin (IL)‐1β and IL‐17 and the presence of mutations in the main genes involved in autoinflammation indicate that PG is a polygenic autoinflammatory condition, as previously demonstrated in PASH. The involvement of proinflammatory cytokines could address the use of biological drugs blocking IL‐1 or IL‐17 in patients with refractory PG and in patients with PASH. Summary: Background: Pyoderma gangrenosum (PG) is a rare skin disease characterized clinically by ulcers with undermined borders, and histologically by neutrophil‐rich infiltrates. PG may occur alone, in syndromic forms or associated with systemic diseases, such as inflammatory bowel disease and haematological or rheumatological disorders. Objectives: To determine a specific genetic background related to autoinflammation for PG. Methods: We assessed autoinflammation by evaluating the cytokine profile and genes involved in classic autoinflammatory diseases in 13 patients with PG and in seven patients with the syndromic form, known as PASH (pyoderma gangrenosum, acne and suppurative hidradenitis). Results: In skin samples, the expression of interleukin (IL)‐1β and its receptors, IL‐17 and its receptor, and tumour necrosis factor‐α and its receptors were significantly higher in both PG ( P = 0·001) and in PASH ( P < 0·001) than in controls. The chemokines IL‐8; chemokine (C‐X‐C motif) ligand 1/2/3; chemokine (C‐X‐C motif) ligand 16; and RANTES (regulated on activation, normal T‐cell‐expressed and secreted) were also overexpressed. Cases of PG and PASH showed mutations in the autoinflammatory genes MEFV, NLRP3, NLRP12, NOD2, LPIN2 and PSTPIP1 . Conclusions: Overexpression of cytokines/chemokines, along with genetic changes, supports the hypothesis that PG and its syndromic form, PASH, are a spectrum of polygenic autoinflammatory conditions.